Influence of different orthodontic upper retainers in speech: analysis by laypersons and acoustic analysis - Higa, Rodrigo Hitoshi (2018)
Introduction: The aim of this study was to evaluate the influence of different upper retainers in speech, through Perceptual Auditory Analysis by the laypersons and acoustic analysis. Methods: Eighteen volunteers were selected to use four types of upper retainers: conventional Wrap-Around (CWA), modified horseshoe Wrap-Around (HWA), modified anterior hole Wrap-Around (AHWA) and vacuum-formed (VF). They were used for 21 days each, with intervals of 7 days without use among them. Speech evaluation was performed in vocal excerpts recordings made before installation of the retainers (T0), immediately after the installation of each retainer (T1), and 21 days after the installation (T2). The Perceptual Auditory Analysis of laypersons was performed by means of the visual analogue scale of 100 mm, while the acoustic analysis consisted of the mean diadochokinesia (DDK) rate evaluation, as well as the formant frequencies F1 and F2 of the fricative consonants. One-way ANOVA and two-way ANOVA were used. Results: In the Perceptual Auditory Analysis of laypersons, there was a worsening in the values of T0 to T1 in all the retainers, but only for CWA and VF the values were statistically lower. In T2 the values increased, but for the VF the value still remained statistically lower than T0 while for the AHWA the difference of T0 for T2 was practically null. There were no changes in DDK values. For the formant frequencies, in general way there was a difference from T0 to T1 and a little difference from T0 to T2, whereas in the comparison among the devices the CWA presented greater changes in the F1 formants of some consonants, whereas AHWA presented lower values, with the others devices showing intermediate values. Conclusions: In both types of analysis (subjective and objective), there was a change in speech after the installation of each retainer, with an improvement after 21 days of use. The laypersons considered larger speech disorders involving VF, and smaller ones involving AHWA. For the acoustic analysis, the changes were greater for CWA, whereas for AHWA there were lower changes.